A new species of Clonostachys (Bionectriaceae) from Southwest China - Zhao, Yun-Wei; He, Shu-Cheng; Shi, Yuan-Ji; Wu, Ting; Zhang, Ying (Phytotaxa, 2025)
Clonostachys xishuangbannaensis is an endophytic fungus isolated from fresh and healthy leaves collected in Xishuangbanna, Yunnan Province, China. It is characterized by solitary, raised, and sparse colonies, mononematous, straight or flexuous, penicillate, and erect conidiophores, and monophialidic, terminal, flask-shaped to cylindrical, aseptate, hyaline phialides. The conidia are single-celled, solitary, acrogenous, simple, and ellipsoidal to oblong with obtuse ends. The species exhibits morphological features typical of the genus Clonostachys. Phylogenetic analyses based on concatenated sequences of the 28S rDNA, translation elongation factor 1-alpha (tef1), RNA polymerase II subunit 2 (rpb2), internal transcribed spacer (ITS), and β-tubulin (tub2) genes, supplemented by morphological assessment, confirmed that C. xishuangbannaensis represents a distinct monophyletic lineage within the genus. Considering the integrated phylogenetic and morphological evidence, we formally propose it as a new species of Clonostachys. This study significantly enhances the understanding of fungal diversity in the previously underexplored region of Yunnan Province, China.